1983
DOI: 10.1111/j.1471-4159.1983.tb08108.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Cathepsin D in Rat Neural Tissue

Abstract: Cathepsin D, an aspartyl endopeptidase, was analyzed in cortex from forebrain and cerebellum, spinal cord, and optic and sciatic nerves, and in the liver of rats from 1 to 120 days of age. Cathepsin D was quantitated in tissue extracts by measurement of enzyme specific activity on a substrate of [methyl‐14C]‐methylated hemoglobin and by radioimmunoassay. Immunocytochemistry was used to ascertain the identity of the mixed cell types that contributed to the cathepsin D detected. As quantitated by radioimmunoassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…The increase of CD seen here was similar to the increase of specific activity of two other lysosomal enzymes from C6 cells grown under comparable conditions (Wallace and McCormick, 1982). Previous studies (Whitaker et al, 1980;Snyder and Whitaker, 1983) from whole tissue have shown that CD measured by RIA parallels that of CD specific activity. It is known from in vitro translation studies of mouse and porcine spleen CD mRNA (Erickson and Blobel, 1979;Rosenfeld et al, 1982) that the initial product of translation is a glycoprotein with an M, of greater than 50 kD.…”
Section: Changes In Molecular Species Of CDmentioning
confidence: 83%
See 2 more Smart Citations
“…The increase of CD seen here was similar to the increase of specific activity of two other lysosomal enzymes from C6 cells grown under comparable conditions (Wallace and McCormick, 1982). Previous studies (Whitaker et al, 1980;Snyder and Whitaker, 1983) from whole tissue have shown that CD measured by RIA parallels that of CD specific activity. It is known from in vitro translation studies of mouse and porcine spleen CD mRNA (Erickson and Blobel, 1979;Rosenfeld et al, 1982) that the initial product of translation is a glycoprotein with an M, of greater than 50 kD.…”
Section: Changes In Molecular Species Of CDmentioning
confidence: 83%
“…For radioimmunoassay (RIA), the cells were washed once with PBS, removed by scraping, pelleted by centrifugation, and washed twice with PBS. Cell pellets were prepared for RIA as described previously (Snyder and Whitaker, 1983).…”
Section: Materials and Methods Culture And Treatment Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the culture period, CM was removed and 1 ml of 0.1 M Tris-acetate, pH 7.2, containing 0.1 % Triton X-100 was added and the sample sonicated (Whitaker et al, 1983a,b). Cathepsin D protein was then quantitated by a double antibody radioimmunoassay using absorbed rabbit (R 164) antirat cathepsin D (Snyder et al, 1983;Whitaker et al, 1983a,b). The immunoreactive cathepsin D and the cathepsin D enzyme activity was related to the total protein concentration determined by the Bradford method (BioRad).…”
Section: Measurement Of Immunoreactive Cathepsin D In Astrocytesmentioning
confidence: 99%
“…Because there is no known intra-cellular inhibitor olf cathepsin D in mammals, the cellular level of the enzyme and its response to external stimuli should have a direct relationship to the activity of cathepsin D. The normal nervous system also reflects the wide but uneven distribution of cathepsin D among its cell types (Whitaker el. al., 1981;Snyder and Whitaker, 1983;Whitaker and Crowley, 1983;Snyder et al, 1985). The normal controls and pathological events influencing cathepsin D content among cells in neural tissue are unknown.…”
mentioning
confidence: 99%